Trazos de economía nueva : Parte II. Preliminares de una ubicación de la política económica - Spinelli, Armando P. (1957)
Economic policy as a systematization of economic activity creates an antinomy if confronted with economic theory whose object is scarcity. An historical study of the evolution of economic theory reveals that cultural sciences, among which also economics, were first included in the methodology of natural sciences during the culmination of rational positivism, which created a mecanistic and organistic conception both of society and its institutions. Thus, as natural sciences are evolving, the particular and most improved methodology is applied to economics. Its classical position always was causal and not teleologic. Any other fundamentation is considered heterodox. Pareto, Cassel and Robbins developed science in accordance with these rules. However, the sciences modify and deepen their postulates, as is the case of epistemologic formulations of cultural sciences, whose laws were formerly those of natural science and are now those of human sciences. In physics, assumptions which are not consistent with reality are discarded but in economics they are still maintained. We operate with facts and postulates belonging to the reality of the capitalistic system. Although this system is already outdated to a great extent. Therefore it is difficult to accept a nonteleologic position without normative and valuative implications.